2016
DOI: 10.1016/j.jclepro.2015.03.071
|View full text |Cite
|
Sign up to set email alerts
|

Residents' behaviour as a function of cognitive appraisals and affective responses toward a petrochemical industrial complex

Abstract: Please cite this article as: López-Navarro MÁ, Llorens-Monzonís J, Tortosa-Edo V, Residents' behaviour as a function of cognitive appraisals and affective responses toward a petrochemical industrial complex, Journal of Cleaner Production (2015), doi: 10.1016/j.jclepro.2015.03.071. This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 112 publications
(69 reference statements)
1
5
0
Order By: Relevance
“…First, convergent validity requires a factor loading of greater than 0.500, but 0.498 was accepted as approximate to the threshold of 0.500 and was highly significant (p < 0.001). In addition, the average variance extracted (AVE) should be above 0.500 for all latent variables, which says that at least 50% of measurement variance is explained [71]. Table 2 shows that all AVEs ranged from 0.511 to 0.813.…”
Section: Measurement Modelmentioning
confidence: 97%
“…First, convergent validity requires a factor loading of greater than 0.500, but 0.498 was accepted as approximate to the threshold of 0.500 and was highly significant (p < 0.001). In addition, the average variance extracted (AVE) should be above 0.500 for all latent variables, which says that at least 50% of measurement variance is explained [71]. Table 2 shows that all AVEs ranged from 0.511 to 0.813.…”
Section: Measurement Modelmentioning
confidence: 97%
“…Research on the relationship between industry and local communities has also looked into the dual role industries play in sustaining local economies and influencing people's quality of life (e.g. Castán-Broto, 2013;López-Navarro et al, 2016). The abovementioned study found that residents near the Tarragona petrochemical complex had more positive perceptions in both dimensions (higher economic benefits and lower risk); the Tarragona residents also reported higher levels of trust in the way firms manage risk, a variable traditionally associated with risk perception in the literature (Siegrist, 2000;Ter Huurne and Gutteling, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…One possible reason why people attribute greater importance to negative events may be because of their extreme aversion to losses and costs (Kahneman and Tversky, 1984). In this vein, and in relation to the petrochemical industry, López-Navarro et al (2016) showed that residents prioritise environmental issues over economic ones in their behavioural intentions, thus endorsing the argument that the damage of a loss (environmental costs) tends to outweigh the benefits (economic consequences). Apart from the relative importance of both factors, recall that the results of the confirmatory factor analysis showed a negative correlation between judgements of risk and benefit, a correlation already highlighted in previous studies (e.g., Alhakami and Slovic, 1994;Siegrist et al, 2000).…”
Section: Discussionmentioning
confidence: 94%